When Courts do Politics: Public Interest Law and Litigation in East Africa by J Oloka- Onyango - Mungai, Melissa (Strathmore Law Review, 2018)
An all-too-simplistic appreciation of the relationship among the three arms of government should be excluded in order to get the gist of Oloka’s writing. He pulls apart the idea that courts simply interpret the law, keeping off from legislative and executive duties. Instead, the author introduces the notion that courts are not insulated from the ‘waves of politics’. In this regard, he invites scrutiny of their powers: of judicial review, to declare a law invalid, to appoint and vet judges, and to interpret the constitution. These defy a purist understanding of the classical separation of powers theory which holds that ‘judges should just judge’ and in this sense avoid upsetting the status quo.